Previous infection with Staphylococcus aureus strains attenuated experimental encephalomyelitis - Donega Franca, Thais Graziela [UNESP]; Chiuso-Minicucci, Fernanda [UNESP]; Goncalves Zorzella-Pezavento, Sofia Fernanda [UNESP]; Watanabe Ishikawa, Larissa Lumi [UNESP]; Rosa, Larissa Camargo da [UNESP]; Colavite, Priscila Maria [UNESP]; Marques, Camila; Ikoma, Maura Rosane Valerio; Ribeiro de Souza da Cunha, Maria de Lourdes [UNESP]; Sartori, Alexandrina [UNESP] (Biomed Central Ltd., 2014)
Background: Bacterial superantigens are potent T cell activators that can activate T cells with specificity for antigens of the central nervous system (CNS). In this study, we compared the effect of two S. aureus strains on experimental autoimmune encephalomyelitis (EAE) development. C57BL/6 female mice were infected with S. aureus ATCC 51650, which produces toxic shock syndrome toxin 1 (TSST-1+) or S. aureus ATCC 43300, which does not produce toxins (TOX-). Three days later, the animals were subjected to EAE induction by immunization with myelin oligodendrocyte glycoprotein (MOG). The weight variation, disease incidence and clinical score were recorded daily. Cytokines and Foxp3+ regulatory T cells in the brain were evaluated during the acute disease phase. Cytokines and Foxp3+ regulatory T cells in the spleen and histopathological analysis of the CNS were assessed during the chronic stage.Results: Previous infection with both strains similarly decreased the clinical score; however, only the TSST-1+ strain clearly diminished inflammation in the CNS. The infections also modulated cytokine production in the spleen and CNS. Reduced production of IL-5 and IL-10 was detected in MOG-stimulated spleen cultures in the TOX- and TSST-1+ infected groups, respectively. In S. aureus stimulated cultures, there was an increased production of IFN-gamma and IL-10 in both infected groups and an increased level of IL-5 in the TSST-1+ group. CNS infiltrating cell cultures from previously infected mice produced less IL-17 in response to MOG and more IFN-gamma in response to S. aureus stimulation.Conclusions: These results indicated that both strains attenuated clinical EAE manifestations, but only TSST-1 clearly decreased CNS inflammation.
Keywords: S. aureus; Experimental autoimmune encephalomyelitis; Toxic shock syndrome toxin 1